Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 169679 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Coccinellidae", "Country is United Kingdom of Great Britain and Northern Ireland", "HasGeospatialIssue is false", "HasCoordinate is true", "BasisOfRecord is Observation" ] } The dataset includes 169679 records from 55 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007869-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences